Krystyna Duraj-Nowakowa, Pisarstwo naukowe: między rzemiosłem a sztuką, Oficyna Wydawnicza „Humanitas”, Sosnowiec 2015, ss. 359. - Klasińska, Barbara (Horyzonty Wychowania, 2015)
O potrzebie maestrii pisarstwa naukowego